2018
DOI: 10.1371/journal.pone.0203470
|View full text |Cite
|
Sign up to set email alerts
|

Questionable research practices in student final theses – Prevalence, attitudes, and the role of the supervisor’s perceived attitudes

Abstract: Although questionable research practices (QRPs) and p-hacking have received attention in recent years, little research has focused on their prevalence and acceptance in students. Students are the researchers of the future and will represent the field in the future. Therefore, they should not be learning to use and accept QRPs, which would reduce their ability to produce and evaluate meaningful research. 207 psychology students and fresh graduates provided self-report data on the prevalence and predictors of QR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(100 citation statements)
references
References 67 publications
9
82
2
7
Order By: Relevance
“…While only a minority of students interviewed referred to this tension, the findings highlight the need for supervisors to not let their own disappointment translate into poorer supervision when students' research is not publishable. One participant reported "fishing" for significant results, aligning with recent research reporting that supervisors shape students' attitudes toward questionable research practices (Krishna and Peter, 2018). Student engagement in questionable research practices has also been documented earlier in the undergraduate degree (Rajah-Kanagasabai and Roberts, 2015), further highlighting the need for supervisors to clearly articulate best practices and demonstrate these in their own research.…”
Section: Inconsistenciessupporting
confidence: 68%
“…While only a minority of students interviewed referred to this tension, the findings highlight the need for supervisors to not let their own disappointment translate into poorer supervision when students' research is not publishable. One participant reported "fishing" for significant results, aligning with recent research reporting that supervisors shape students' attitudes toward questionable research practices (Krishna and Peter, 2018). Student engagement in questionable research practices has also been documented earlier in the undergraduate degree (Rajah-Kanagasabai and Roberts, 2015), further highlighting the need for supervisors to clearly articulate best practices and demonstrate these in their own research.…”
Section: Inconsistenciessupporting
confidence: 68%
“…Extending this perspective, we believe that exploring psychology students' statistical reporting quality and indications of QRPs would be just as important, as their behaviour reflects our quality of teaching and they are tomorrows’ early-career researchers in psychological science. We are aware of a single recent study that investigated psychology students' self-reported behaviour and attitudes regarding QRPs [31]. These survey results revealed an average QRP self-admission rate of 9% over 11 different practices, while behaviours such as selective reporting of studies that worked, 1 data exclusions after looking at the data and HARKing had rates of 15% and higher.…”
Section: Introductionmentioning
confidence: 99%
“…These reported QRP self-admission rates of students are lower than those of academic researchers [9,10]. 2 However, Krishna & Peter [31] discuss the possibility that students’ self-admission rates might underestimate actual QRP prevalences in student theses. It therefore remains unclear to what extent students' actual behaviour reflects sacrifices of scientific rigor to achieve significant results, considerations about statistical power and correct statistical reporting when writing their final thesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Des comptes rendus de cours plus classiques délivrés à ce sujet à destination des étudiants en psychologie attestent de leur valeur pédagogique (Blincoe & Buchert, 2020 ;Chopik et al, 2018). Pour finir, il ne faut pas oublier le rôle important des encadrants de thèse dans la sensibilisation et la formation des doctorants sur ces questions (Krishna & Peter, 2018).…”
Section: Des Initiatives De Grande Ampleurunclassified